Reciclador de energia para testes de burn-in em fontes CC para telecomunicações - Dantas, Joacillo Luz (2006)
The present work approaches a feasible architecture to accomplish the telecomunications DC power source burn-in teste using the energy recycler concept. The topology is composed by three eletronic converters and replaces the regular resistor load bank that is used in conventional burn-in test. The energy recicler drains of the DC power source the current demanded during the burn-in test but it returns to the utility grid the most energy taken out from the DC source by a high power factor and low Total Harmonic Distortion currente injection.